AKSES PEREMPUAN PENGUNGSI BENCANA GUNUNG SINABUNG DAN UPAYA PENINGKATAN EKONOMI KELUARGA DI DAERAH SIOSAR KABUPATEN KARO - Juliana br Simbolon br Simbolon; Rikawati Ginting Munthe; Maya Sari (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2018)
In the current study; entitled "Women's Access to Disaster Refugees in Mount Sinabung and Efforts to Improve Family Economy in the Siosar Region of Karo Regency" which need to be examined are: First; Access to disaster IDP women from Mount Sinabung is affected; The first; a. Fixed and sufficient income, b. Good health, c. Eat enough nutrition, d. A decent residence, e. Minimum elementary education, f. Adequate clean water, g. Good sanitation, and g. Adequate child and elderly support, it is suspected that the percentage is still low. And secondly; Significant factors affecting the improvement of the family economy of the disaster refugee women of Mount Sinabung are productive age factors, education above junior high school, factors of working long over 3 years, number of small children, small number of dependents, permanent employment status, married status and type of husband's work .The basic method used in this research is descriptive research method. The area sampling method was purposively in the Siosar refugee area of Brastagi which had a large proportion of disaster IDP women in Mount Sinabung compared to other refugee relocations. Sampling using purposive sampling method involving 60 female respondents of refugees who were in the refuge of Mount Sinabung, Karo Regency.Data collection was conducted by interview using interview guidelines to reveal various efforts that have been made in handling the social psychological impact of victims of the Sinabung volcano disaster. Observation on the condition of refugees in refugee camps and review of documents related to the condition of the area and the number of victims. Furthermore, the collected data were analyzed using qualitative descriptive.